Why the time is ripe for an education revolution - Lillard, Angeline S. (Frontiers in Developmental Psychology, 2023)
Most American classrooms employ a teacher-text-centered model of instruction that is misaligned with the developmental science of how children naturally learn. This article reviews that science and the origins of the common instructional model, including three modifications intended to make it work better (grades, age-graded classrooms, and high-stakes testing) yet which time has shown are problematic. Considering scientific theory change, I show how parallel circumstances exist between the situation in education today and pre-Copernican astronomy, building the case that education is now ripe for a paradigm shift in its instructional model, away from teacher-text-centered learning and to highly structured instructional environments that support self-construction through limited free choice. One proven model that responds to our world’s contemporary needs is described, and a prescription is offered for how to bring about a paradigm shift in educational practice.